VALIDITY OF VISUAL ASSESSMENT OF NEONATAL JAUNDICE FOR SCREENING SIGNIFICANT HYPERBILIRUBINAEMIA - Shafiq, Muhammad Faisal; Ahmed, Zeeshan; Ahmad, Asad Maqbool (Pakistan Armed Forces Medical Journal, 2019)
Objective: To determine the validity of absence of visual jaundice below nipple line in ruling out significant neonatal hyperbilirubinaemia. Study Design: Cross-sectional study. Place and Duration of Study: PNS Shifa Hospital Karachi Pakistan, from Jan to Aug 2017. Patients and Methods: A total of 284 babies with ages ranging between 2-7 days, more than 35 weeks of gestation and more that 2000 grams of weight, were enrolled. Visual assessment of dermal jaundice was done in these neonates by a trained pediatric resident. Two zones were arbitrarily defined; one above nipple line and the other below it. The point of most distal dermalicterus was recorded on proforma mentioning the corresponding zone. Serum samples were then sent for laboratory measurement of total bilirubin within one hour of visual assessment. Jaundice in these zones was compared with corresponding total serum bilirubin. Significant hyperbilirubinaemia was defined as total serum bilirubin (TSB) more than 205 micromol/litre. Results: Parents of 4 babies (1.61%) did not give consent for the blood test and 31 babies (10.91%) were lost to follow up. Data of remaining 249 neonates revealed that absence of visual jaundice below the nipple line had sensitivity of 100% and specificity of 73.23% in ruling out significant hyperbilirubinaemia. Conclusion: Absence of jaundice below the nipple line was a reliable screening tool for screening significant hyperbilirubinaemia after 24 hours of age in otherwise healthy babies more than 35 weeks of gestation and more than 2000 grams of weight.